Philosophical Thoughts of Ibn Sina: Synergy of Greek Philosophy with Islamic Thought - Ingeu Siti Aisyah; Rizqi Nazwa Ramdani; Siti Fitria Firmansyah (Al-Falsafah: Jurnal Pemikiran dan Filsafat Islam, 2025)
This Article discusses the life and intellectual contributions of Ibn Sina or Avicenna, one of the greatest figures in the history of Islamic philosophy and medicine. The main focus of this article is his thoughts on existence and essence, as well as the theory of emanation, which successfully synthesized Greek philosophy with Islamic thought. The Article also highlights Ibn Sina’s influence on the development of medieval philosophy and science, both in the Islamic world and the west, makin his legacy remain, relevant to this day.